Cation-substitution induced stable GGAG:Ce3+ ceramics with improved optical and scintillation properties. Issue 15 (December 2017) - Zhang, Ji-Yun; Luo, Zhao-Hua; Liu, Yong-Fu; Jiang, Hao-Chuan; Jiang, Jun; Liu, Guo-Qiang; Zhang, Jing-Xian; Qin, Hai-Ming
Abstract: Among the aluminate garnet materials, cerium doped gadolinium gallium aluminum garnet ceramics (GGAG:Ce) have shown great performance advantages, which suggests their promising applications in medical imaging, high energy rays detection and high power LED lighting. The goal of this work is to raise the thermostability of GGAG:Ce by means of partial Y 3+ substitution, and to find out the relationship between the crystal structure and the optical properties. GGAG:Ce 3+, xY 3+ ceramics were prepared via chemical precipitation, and a combination of sintering in oxygen atmosphere and hot isostatic pressing. In order to identify the detailed crystal structure information, Rietveld refinements were first taken on the XRD patterns. Crystal structure refinements verify the ability of mutual substitution of Y and Ga atoms between the dodecahedron and octahedral sites. The optical, luminescent and scintillation properties have been investigated. Results show that the transmittance of the sample can reach 77% at the emission peak wavelength, while the spectrally corrected light yield value reaches 61, 000 ± 1200 photons/MeV.